The Prevention of Gross Human Rights Violations Under International Human Rights Law - van der Have, Nienke (2018)
This book contains a systematic assessment of the content and scope of obligations to prevent gross human rights violations. There has been a great deal of attention for concepts aiming to prevent gross human rights violations, such as conflict prevention and the responsibility to protect. Yet despite this shift in attention towards prevention, it has remained unclear what legal obligations states have to prevent gross human rights violations under international human rights law. The focus in this book is on three specific types of injury prohibited under international human rights law: torture, arbitrary death and genocide. Further distinctions are made between four temporal phases (long-term prevention, short-term prevention, preventing continuation, preventing recurrence) and territorial and extraterritorial obligations. The structure of the book allows academics and practitioners to learn about obligations to prevent gross human rights violations in a general sense, as well as find targeted information on the content and scope of obligations in specific settings. Nienke van der Have recently completed her Ph.D. at the Amsterdam Center for International Law, which forms part of the University of Amsterdam's Faculty of Law, and currently works as Senior legal specialist at the department of Constitutional Affairs and Legislation of the Ministry of the Interior and Kingdom Relations of The Netherlands.
Chapter 1. Introduction -- Chapter 2. Obligations to Prevent Within State Territory -- Chapter 3. Extraterritorial Obligations to Prevent Based on Jurisdiction -- Chapter 4. Extraterritorial Obligations to Prevent Beyond Jurisdiction -- Chapter 5. Conclusion -- Index.
Keywords: Human rights; International criminal law; International humanitarian law; International law; Peace; War Crimes; Human Rights; Conflict Studies; International Criminal Law .; International Humanitarian Law, Law of Armed Conflict; Sources and Subjects of International Law, International Organizations; War Crimes